PREVALENCE OF ECTOPARASITES INFESTATION AMONG SOME BREEDS OF CHICKENS IN ALQAHIRA, AKKO L. G. A, GOMBE STATE - Muhammed, Ishaku; Idris, Usman; Ahmanullah Aminu, Abubakar; Ibrahim, Mubarak; Sulaiman Bose, Muhammad; Abdurrahman, Nazifi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Ectoparasitism has been identified as one of the major factors that threaten scavenging village chicken production systems in developing countries. The study examined the prevalence of ectoparasite infestation among chickens in Alqahira quarters in Akko local government, Gombe State. Two hundred chickens, which comprise three species namely: Naked neck, Venda and Ovambo of both sexes and various ages were sampled. Household with moderate to high numbers of chicken population and that were willing to voluntarily cooperate with the sampling procedures were randomly selected and included in the study, Sampling was carried out for a period of 2 months on weekly basis. Ectoparasites were collected from the body/skin of each bird and not from the ground in order to minimize accidental collections of other arthropods that do not actually parasitize chickens. Examination for ectoparasitic infestations was carried out early in the morning and in the evening. The result of ecto parasite infestation based on experimental site showed that Wurro bogga community has the highest number of chicken examined 80 (40%) and also the highest infestation 55 (68.75%). The result also showed that out of 200 chickens examined, 108 representing 54.0% were found to be infested with ectoparasite with female constituting the highest infestation 70 (64.81%) and males 38 (35.19%). The result further revealed that lice were found to be more abundant 48 (44.44%) followed by mites 28 (25.93%), fleas 17 (15.74%) and the least parasite was ticks 15 (13.89%) respectively. The result of the distribution of the ectoparasite based on breed revealed that venda chickens were found to be more infested 40 (37.04%) than ovambo 39 (36.11%) and naked neck 29 (26.85%), respectively. Application of integrated prevention and control measures like awareness creation to the community on the overall effect of ectoparasites on the productivity of chickens and prevention methods and further studies to cover investigation of endoparasites of chickens in the study area should be explored